Synthesis and molecular characterization of polythiophene block Co-, ter-polymers and four-arm star homopolymer - Grana, Eftychia; Katsigiannopoulos, Dimitrios; Avgeropoulos, Apostolos; Goulas, Vlasios (My University, 2008)
We report the synthesis of polythiophene (PT) block copolymers with polystyrene (PS) or polyisoprene of increased 3,4 microstructure (PI3,4) and triblock terpolymer of the PS-b-PI-b-PT type. Tetrathienylsilane (C16H12S4Si) was also prepared in order to react with thiophene and eventually synthesize a four-arm star PT homopolymer. The preparation of the functional precursors and intermediate products (PS, PI, PS-b-PI3,4, and C16H12S4Si) was achieved through high vacuum techniques, and PT was synthesized under ambient conditions via the corresponding chemical oxidative polymerization reaction. The final polymers and the intermediate precursors were molecularly characterized by size exclusion chromatography (SEC), membrane osmometry (MO), proton nuclear magnetic resonance (1H-NMR), and carbon nuclear magnetic resonance (13C-NMR) spectroscopies.
Keywords: Block copolymers-terpolymer; Oxidation-anionic polymerization; Polythiophene; Star homopolymer